2022
DOI: 10.5194/tc-2022-84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic sea ice and snow from different ice models: A CICE–SI3 intercomparison study

Abstract: Abstract. Sea ice models fill many purposes. They are used in global climate models or for short term forecasts to plan shipping routes. No matter what their output is used for, understanding the cause for there variability is crucial. In the this study two commonly used sea-ice models, CICE and SI3 were compared after running both models with similar boundary condition, on the same grid, with the same forcing and initialised with the same data, with the aim to understand how the two models differ from each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
1
0
4
Order By: Relevance
“…Several sea-ice models of the Arctic, like CICE (Hunke et al, 2017) and SI3 (Sievers et al, 2022), are concurrently developed for operational purposes: short-term predictions for maritime road and weather forecast as well as long-term simulations for climate projections. The recent development of models based on brittle rheologies (Girard et al, 2011;Rampal et al, 2016;Dansereau et al, 2016), like neXtSIM, can represent the observed effects of small-scale processes onto the resolved mesoscale with ∼ 10 km horizontal resolution (Bouchat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several sea-ice models of the Arctic, like CICE (Hunke et al, 2017) and SI3 (Sievers et al, 2022), are concurrently developed for operational purposes: short-term predictions for maritime road and weather forecast as well as long-term simulations for climate projections. The recent development of models based on brittle rheologies (Girard et al, 2011;Rampal et al, 2016;Dansereau et al, 2016), like neXtSIM, can represent the observed effects of small-scale processes onto the resolved mesoscale with ∼ 10 km horizontal resolution (Bouchat et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Она образуется в результате смывания верхней части плодородной земли под влиянием дождей, льдов, протекающих вод, ветра, малого снега и других водных потоков. В зависимости от распространения водного потока, бывает линейная или поверхностная водная эрозия [4].…”
unclassified
“…Из-за своей незаметности она очень опасна и часто наблюдается на полях, расположенных на склонах с разным уклоном. В зависимости от условий, с одного гектара пашни может смыться от 5 до 25 тонн почвы, а в некоторых районах этот показатель может достигать 30-50 тонн/га [4]. В течение нескольких лет пахотный слой может уменьшиться на половину или даже более, что приводит к непригодности полей.…”
unclassified
See 2 more Smart Citations